ZEITLUPE positively regulates hypocotyl elongation at warm temperature under light in Arabidopsis thaliana - Miyazaki, Yuji; Takase, Tomoyuki; Kiyosue, Tomohiro (Plant signaling & behavior, 2015)
Hypocotyl cell elongation has been studied as a model to understand how cellular expansion contributes to plant organ growth. Hypocotyl elongation is affected by multiple environmental factors, including light quantity and light quality. Red light inhibits hypocotyl growth via the phytochrome signaling pathways. Proteins of the FLAVIN-BINDING KELCH REPEAT F-BOX 1 / LOV KELCH PROTEIN 2 / ZEITLUPE family are positive regulators of hypocotyl elongation under red light in Arabidopsis. These proteins were suggested to reduce phytochrome-mediated inhibition of hypocotyl elongation. Here, we show that ZEITLUPE also functions as a positive regulator in warmth-induced hypocotyl elongation under light in Arabidopsis.